Pengaruh Citra Merek dan Gaya Hidup terhadap Keputusan Pembelian Iphone pada Mahasiswa Universitas Bina Darma - Herdian Prahmana Putra; Efan Elpanso (Universitas Batanghari, 2023)
Iphone is well-known as a high-end cellphone in Indonesia, but because of this there are many fake iphone products or iphone units whose components have been replaced (reconditioned/refurbished) and are sold at low prices. In addition, most iPhone users buy only to fulfill their lifestyle, not because of their needs. The purpose of this study was to determine the effect of brand image and lifestyle on iphone purchasing decisions for Bina Darma University students. The population in this study were Bina Darma University students who purchased iphones, the sample size in this study was 100 Bina Darma University students. This study uses primary data obtained from questionnaires and the analysis technique used is the classical assumption test, multiple regression analysis, correlation coefficient and determination. The results of this study indicate that brand image and lifestyle simultaneously have a significant effect on iphone purchasing decisions at Bina Darma University students with the results of the F-count test of (59,671) > F table (3.09) with a significance level of 0.000 <0.05.